Modification method of high-capacity zinc and magnesium ion doped lithium iron vanadium phosphate positive electrode material

By using aqueous hydrogen peroxide solution as the ball mill dispersant, a high-capacity zinc-magnesium ion-doped lithium vanadium iron phosphate positive electrode material was prepared, which solved the problems of large energy consumption and high cost in the prior art, and achieved improvement of material performance and reduction of cost.

CN119786579AActive Publication Date: 2025-04-08HEILONGJIANG ELECTRIC POWER SCIENCE RESEARCH INSTITUTE +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510003310.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-08
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

During the preparation process of the existing lithium vanadium phosphate material doped with metal ions, the energy consumption is high, the cost is high, and the electronic conductivity of the material is low, which limits its application.

Method used

A carbon-coated zinc and magnesium ion doped lithium vanadium phosphate precursor material was prepared by ball milling method, and gradient high-temperature calcination was performed under an inert gas atmosphere to prepare a high-capacity zinc-magnesium ion doped lithium vanadium phosphate positive electrode material.

Benefits of technology

It realizes the refinement of material particles, improves electrochemical performance, reduces production costs, and is simple and safe in process, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786579A_ABST
    Figure CN119786579A_ABST
Patent Text Reader

Abstract

The invention discloses a modification method of a high-capacity zinc and magnesium ion doped lithium iron vanadium phosphate positive electrode material, and belongs to the technical field of lithium ion battery positive electrode materials. The method comprises the following steps: 1, weighing raw materials according to the molar ratio of lithium, vanadium, iron, phosphorus, zinc, magnesium and carbon; 2, preparing a carbon-coated zinc and magnesium ion doped lithium vanadium iron phosphate precursor material; and 3, preparing the zinc and magnesium ion doped lithium iron vanadium phosphate positive electrode material with a chemical formula of Lix + 3Fex-yMgyV2-zZnz (PO4) 3 / C, x = 1-5, y = 0.01-0.2, and z = 0.01-0.05. According to the invention, the electrochemical performance of the material is improved, and the material has high capacity retention ratio and good cycle stability. The preparation process is simple, the production period is shortened, the cost is reduced, the potential safety hazard in the production process is reduced under the condition of ensuring that the positive electrode material has good specific capacity and capacity retention ratio, the equipment price is low, no toxic or harmful substance is released, and the method is suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion battery positive electrode materials, and specifically relates to a modification method for a high-capacity zinc-magnesium ion-doped lithium vanadium iron phosphate positive electrode material. Background Art

[0002] Polyanionic compounds are a general term for a series of compounds containing tetrahedral or octahedral anionic structural units (XOm)n-(X=P, S, As, Mo and W). These compounds have good lithium insertion performance and good safety, so they are the most promising positive electrode materials for the new generation of lithium-ion batteries. Among them, LiFePO 4 It has become a research hotspot due to its rich raw material sources, stable discharge voltage, good thermal stability and excellent cycle characteristics, but LiFePO 4 Not only is the electronic conductivity and tap density low, but the discharge voltage is also low, which limits its further development and application. Li with a monoclinic NASICON (Sodium Super Ion Conductor) structure 3 V 2 (PO 4 ) 3 Compounds have sufficient space to conduct alkali metal ions such as Na and Li, so they have better conductivity than LiFePO 4 Higher diffusion coefficient, and Li 3 V 2 (PO 4 ) 3 The structure is much more stable than that of transition metal oxides, even in the presence of Li + When the molar ratio of Li to transition metal is greater than 1, it still has extraordinary stability. 3 V 2 (PO 4 ) 3 Due to its abundant raw material sources, low cost, good high-rate discharge performance, high safe charging cut-off voltage, good safety, high discharge voltage and specific energy, it has become a new research hotspot and is seen as the most promising positive electrode material for lithium-ion batteries in electric vehicles.

[0003] For lithium iron vanadium phosphate materials, due to the inherent low electronic conductivity problem of polyanionic phosphates, doping with metal ions helps to improve the preferential conduction path of electrons, thereby improving the rate capability and cycle performance of electrode materials. At present, the doping of lithium iron vanadium phosphate materials with metal ions is mainly based on solid-phase ball milling and sol-gel methods. The preparation of lithium iron vanadium phosphate materials doped with metal ions is usually carried out at a high ball milling speed, which consumes a lot of energy. In addition, the calcination temperature is high and the time is long, which consumes a lot of energy and increases the synthesis cost. Lithium-ion batteries face cost problems in the commercialization process. There are many mature lithium iron vanadium phosphate positive electrode materials on the market. The market competition is fierce, and those with outstanding cost performance have an advantage. Therefore, the modified synthesis of lithium iron vanadium phosphate materials doped with metal ions needs to have obvious advantages in both performance and cost in order to compete in the market. Summary of the invention

[0004] The purpose of the present invention is to solve the above-mentioned technical problems and to provide a method for modifying a high-capacity zinc-magnesium ion-doped lithium iron vanadium phosphate positive electrode material.

[0005] A modification method for a high-capacity zinc-magnesium ion-doped lithium iron vanadium phosphate positive electrode material is implemented by the following steps:

[0006] 1. Weighing materials:

[0007] According to the molar ratio of lithium, vanadium, iron, phosphorus, zinc, magnesium and carbon being (3.675-6.825):(0.95-1):(1.8-5):5.5:(0.01-0.05):(0.01-0.2):(4-8), respectively weigh a lithium source, a vanadium source, an iron source, a phosphorus source, a zinc source, a magnesium source and a carbon source;

[0008] 2. Preparation of carbon-coated zinc and magnesium ion-doped lithium iron vanadium phosphate precursor materials:

[0009] The weighed lithium source, vanadium source, iron source, phosphorus source, zinc source, magnesium source and carbon source are added into deionized water and stirred evenly to obtain a mixture, and then the mixture is dispersed into a dispersion medium, and then placed in a ball mill for 7 to 10 hours to obtain a slurry, and after drying and grinding, a carbon-coated zinc and magnesium ion-doped lithium iron vanadium phosphate precursor material is obtained;

[0010] 3. Preparation of zinc and magnesium ion doped lithium vanadium iron phosphate positive electrode material:

[0011] The carbon-coated zinc and magnesium ion-doped lithium iron vanadium phosphate precursor material is transferred to a tube furnace and subjected to gradient high-temperature calcination under an inert gas atmosphere. After the calcination, it is naturally cooled to room temperature, and then ground and sieved to obtain a high-capacity zinc and magnesium ion-doped lithium iron vanadium phosphate positive electrode material with a chemical formula of Li x+3 Fe x-y Mg y V2-z Zn z (PO 4 ) 3 / CC, and x=1-5, y=0.01-0.2, z=0.01-0.05, the modification method is completed.

[0012] Furthermore, in step one, the lithium source is lithium carbonate; the vanadium source is vanadium pentoxide; the iron source is ferrous oxalate dihydrate; the phosphorus source is ammonium dihydrogen phosphate; the zinc source is zinc oxide; the magnesium source is magnesium nitrate, magnesium acetate, magnesium sulfate or magnesium oxide; and the carbon source is sucrose, glucose or citric acid monohydrate.

[0013] Furthermore, the dispersion medium in step 2 is a hydrogen peroxide aqueous solution with a volume fraction of 1% to 5%; and the dispersion method is electromagnetic stirring.

[0014] Furthermore, in step 2, the ratio of the total mass of the lithium source, vanadium source, iron source, phosphorus source, magnesium source, zinc source and carbon source to the volume of the dispersion medium is 1 g: (5 mL to 15 mL).

[0015] Furthermore, the ball milling temperature in step 2 is 20-25° C., and the rotation speed is 400-600 r / min.

[0016] Furthermore, the ball mill in step 2 uses steel balls, agate balls or zirconia balls, and the ball-to-material mass ratio is 20:1.

[0017] Furthermore, the drying in step 2 is carried out in a forced air drying oven at 80 to 120° C. for 12 to 15 hours; and the grinding is carried out in an agate mortar for 20 to 30 minutes.

[0018] Furthermore, the gradient high temperature calcination in step three is: heating to 300-400°C at a rate of 4-8°C / min, and keeping warm for 6-10h; after the insulation is completed, heating to 750-850°C at a rate of 4-8°C / min, and keeping warm for 6-10h.

[0019] Furthermore, the inert gas in step three is argon; and the screening uses a 400-mesh sieve.

[0020] The beneficial technical effects of the present invention are as follows:

[0021] (1) In the present invention, an aqueous solution of hydrogen peroxide is used as a ball milling dispersant to completely dissolve the raw materials and fully mix them during the ball milling process to obtain a LFMVZP / C sample with a small particle size and relatively uniform particle size. Since the addition of hydrogen peroxide to vanadium pentoxide forms a wet gel, the uniformity of the raw materials at the molecular level is improved, thereby allowing the raw materials to be mixed more uniformly during the ball milling process. In addition, since hydrogen peroxide can accelerate the formation of ammonium vanadate, this can improve the reaction activity of the precursor and shorten the sintering time.

[0022] (2) Magnesium ion doping

[0023] The particle size of the sample prepared by magnesium ion doping is concentrated around 1 μm. After doping, the particle size of the material becomes smaller, which is conducive to the penetration of the electrolyte and has a positive effect on the electrochemical performance of the material. 2+ Doping can refine the particle size of LFMVZP / C material, so the diffusion distance of lithium ions in the LFMVZP / C lattice structure is shortened, thereby improving the electrochemical performance of the material.

[0024] (3) Zinc ion doping

[0025] The charge and discharge test of zinc ion doped lithium vanadium iron phosphate cathode material showed that the prepared LFMVZP / C had a higher first discharge specific capacity and capacity retention rate. The initial discharge specific capacity at 2C current density was 118.35 mAh g -1 After 50 cycles, the LFMVZP / C material can release 117.43 mAh g -1 The reversible capacity of the battery is very high, and the coulombic efficiency during the cycle is close to 100%, with a high capacity retention rate of 99.22% and good cycle stability.

[0026] (4) The preparation process of the present invention is simple, and while ensuring that the positive electrode material has good specific capacity and capacity retention rate, it shortens the production cycle, reduces costs, and reduces potential safety hazards in the production process. The equipment is low-priced and no toxic or harmful substances are released. It has obvious advantages in performance and cost and is suitable for industrial production.

[0027] The invention is suitable for the modification and preparation of high-capacity zinc-magnesium ion-doped lithium iron vanadium phosphate positive electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The XRD diagram of the zinc and magnesium ion doped lithium iron vanadium phosphate positive electrode material in Example 1;

[0029] Figure 2 This is a scanning electron microscope image of the zinc and magnesium ion-doped lithium iron vanadium phosphate positive electrode material in Example 1;

[0030] Figure 3The first figure is a CV curve diagram of the LFVP / C material in Comparative Example 1, and the second figure is a CV curve diagram of the zinc-magnesium ion-doped lithium vanadium iron phosphate positive electrode material in Example 1;

[0031] Figure 4 This is a 2C constant current cycling performance diagram of the zinc and magnesium ion doped lithium vanadium iron phosphate positive electrode material in Example 1;

[0032] Figure 5 This is the AC impedance spectrum of the zinc and magnesium ion doped lithium vanadium iron phosphate positive electrode material in Example 1. DETAILED DESCRIPTION

[0033] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any combination of the specific implementation modes.

[0034] Specific implementation method 1: This implementation method is a modification method of a high-capacity zinc-magnesium ion-doped lithium iron vanadium phosphate positive electrode material, which is achieved by the following steps:

[0035] 1. Weighing materials:

[0036] According to the molar ratio of lithium, vanadium, iron, phosphorus, zinc, magnesium and carbon being (3.675-6.825):(0.95-1):(1.8-5):5.5:(0.01-0.05):(0.01-0.2):(4-8), respectively weigh a lithium source, a vanadium source, an iron source, a phosphorus source, a zinc source, a magnesium source and a carbon source;

[0037] 2. Preparation of carbon-coated zinc and magnesium ion-doped lithium iron vanadium phosphate precursor materials:

[0038] The weighed lithium source, vanadium source, iron source, phosphorus source, zinc source, magnesium source and carbon source are added into deionized water and stirred evenly to obtain a mixture, and then the mixture is dispersed into a dispersion medium, and then placed in a ball mill for 7 to 10 hours to obtain a slurry, and after drying and grinding, a carbon-coated zinc and magnesium ion-doped lithium iron vanadium phosphate precursor material is obtained;

[0039] 3. Preparation of zinc and magnesium ion doped lithium vanadium iron phosphate positive electrode material:

[0040] The carbon-coated zinc and magnesium ion-doped lithium iron vanadium phosphate precursor material is transferred to a tube furnace and subjected to gradient high-temperature calcination under an inert gas atmosphere. After the calcination, it is naturally cooled to room temperature, and then ground and sieved to obtain a high-capacity zinc and magnesium ion-doped lithium iron vanadium phosphate positive electrode material with a chemical formula of Li x+3 Fe x-y Mg y V 2-z Zn z (PO 4 ) 3 / C, and x=1-5, y=0.01-0.2, z=0.01-0.05, the modification method is completed.

[0041] Specific embodiment 2: This embodiment is different from specific embodiment 1 in that the lithium source in step 1 is lithium carbonate; the vanadium source is vanadium pentoxide; the iron source is ferrous oxalate dihydrate; the phosphorus source is ammonium dihydrogen phosphate; the zinc source is zinc oxide; the magnesium source is magnesium nitrate, magnesium acetate, magnesium sulfate or magnesium oxide; the carbon source is sucrose, glucose or citric acid monohydrate. The other steps and parameters are the same as those in specific embodiment 1.

[0042] Specific implementation method 3: This implementation method is different from specific implementation method 1 in that the dispersion medium in step 2 is a hydrogen peroxide aqueous solution with a volume fraction of 1% to 5%; the dispersion method is electromagnetic stirring. The other steps and parameters are the same as those in specific implementation method 1.

[0043] Specific embodiment 4: This embodiment is different from specific embodiment 1 in that the ratio of the total mass of the lithium source, vanadium source, iron source, phosphorus source, magnesium source, zinc source and carbon source to the volume of the dispersion medium in step 2 is 1g:(5mL-15mL). The other steps and parameters are the same as those in specific embodiment 1.

[0044] Specific implementation method 5: This implementation method is different from specific implementation method 1 in that the temperature of the ball mill in step 2 is 20-25° C. and the rotation speed is 400-600 r / min. The other steps and parameters are the same as those in specific implementation method 1.

[0045] Specific implementation example 6: This implementation example is different from specific implementation example 1 in that the ball mill in step 2 uses steel balls, agate balls or zirconium oxide balls, and the ball-to-material mass ratio is 20:1. Other steps and parameters are the same as those in specific implementation example 1.

[0046] Specific embodiment 7: This embodiment differs from specific embodiment 1 in that the drying in step 2 is carried out at 80-120°C in a blast drying oven for 12-15 hours, and the grinding is carried out in an agate mortar for 20-30 minutes. The other steps and parameters are the same as those in specific embodiment 1.

[0047] Specific embodiment eight: This embodiment differs from specific embodiment one in that the gradient high temperature calcination in step three is: heating to 300-400°C at a rate of 4-8°C / min and keeping warm for 6-10h; after the end of the heat preservation, heating to 750-850°C at a rate of 4-8°C / min and keeping warm for 6-10h. The other steps and parameters are the same as those in specific embodiment one.

[0048] Specific embodiment 9: This embodiment is different from specific embodiment 1 in that the inert gas in step 3 is argon gas and the sieving uses a 400-mesh sieve. The other steps and parameters are the same as those of specific embodiment 9.

[0049] Specific embodiment 10: This embodiment is different from the specific embodiment 1 in that in step 3, the high-capacity zinc-magnesium ion-doped lithium iron vanadium phosphate positive electrode material has a chemical formula of Li x+3 Fe x-y Mg y V 2-z Zn z (PO 4 ) 3 / C, and x=4, y=0.08, z=0.05. Other steps and parameters are the same as those in the first embodiment.

[0050] The beneficial effects of the present invention are verified by the following examples:

[0051] Embodiment 1:

[0052] A modification method for a high-capacity zinc-magnesium ion-doped lithium iron vanadium phosphate positive electrode material is implemented by the following steps:

[0053] 1. Weighing materials:

[0054] According to the molar ratio of lithium, vanadium, iron, phosphorus, zinc, magnesium and carbon of 5.775:0.975:3.92:5.5:0.025:0.08:6.325, weigh a lithium source, a vanadium source, an iron source, a phosphorus source, a zinc source, a magnesium source and a carbon source respectively;

[0055] 2. Preparation of carbon-coated zinc and magnesium ion-doped lithium iron vanadium phosphate precursor materials:

[0056] The weighed lithium source, vanadium source, iron source, phosphorus source, zinc source, magnesium source and carbon source are added into deionized water and stirred evenly to obtain a mixture, and then the mixture is dispersed into a dispersion medium, and then placed in a ball mill for 7 hours to obtain a slurry, and after drying and grinding, a carbon-coated zinc and magnesium ion-doped lithium iron vanadium phosphate precursor material is obtained;

[0057] 3. Preparation of zinc and magnesium ion doped lithium vanadium iron phosphate positive electrode material:

[0058] The carbon-coated zinc and magnesium ion-doped lithium iron vanadium phosphate precursor material is transferred to a tube furnace and subjected to gradient high-temperature calcination under an inert gas atmosphere. After the calcination, it is naturally cooled to room temperature, and then ground and sieved to obtain a high-capacity zinc and magnesium ion-doped lithium iron vanadium phosphate positive electrode material with a chemical formula of Li x+3 Fe x-y Mg y V 2-z Zn z (PO4 ) 3 / C, and x=1-5, y=0.01-0.2, z=0.01-0.05, the modification method is completed.

[0059] In step 1 of this embodiment, the lithium source is lithium carbonate; the vanadium source is vanadium pentoxide; the iron source is ferrous oxalate dihydrate; the phosphorus source is ammonium dihydrogen phosphate; the zinc source is zinc oxide; the magnesium source is magnesium oxide; and the carbon source is glucose.

[0060] In step 2 of this embodiment, the dispersion medium is a 3% by volume aqueous solution of hydrogen peroxide; the dispersion method is electromagnetic stirring, and the stirring time is 0.5 h.

[0061] In step 2 of this embodiment, the ratio of the total mass of the lithium source, vanadium source, iron source, phosphorus source, magnesium source, zinc source, and carbon source to the volume of the dispersion medium is 1 g: (5 mL to 15 mL).

[0062] The ball milling temperature in step 2 of this embodiment is 25° C. and the rotation speed is 4000 r / min.

[0063] The ball mill in step 2 of this embodiment uses steel balls, agate balls or zirconia balls, and the ball-to-material mass ratio is 20:1.

[0064] The drying in step 2 of this embodiment is carried out at 80° C. in a forced air drying oven for 12 h; the grinding is carried out in an agate mortar for 20 min.

[0065] The gradient high-temperature calcination in step 3 of this embodiment is as follows: the temperature is raised to 350°C at a rate of 5°C / min and kept at this temperature for 6 hours; after the heat preservation is completed, the temperature is raised to 800°C at a rate of 5°C / min and kept at this temperature for another 8 hours.

[0066] In step three of this embodiment, the inert gas is argon; and the sieving uses a 400-mesh sieve.

[0067] The carbon-coated zinc and magnesium ion-doped lithium iron vanadium phosphate (LFMVZP / C) precursor material obtained in step 2 of this embodiment is in the form of green powder.

[0068] In step 3 of this embodiment, the high-capacity zinc-magnesium ion-doped lithium iron vanadium phosphate positive electrode material has a chemical formula of Li x+3 Fe x- y Mg y V 2-z Zn z (PO 4 ) 3 / C, and x=4, y=0.08, z=0.05.

[0069] Comparative Example 1:

[0070] The method provided in Example 1 is used, except that no Mg and Zn metal compounds are added to the raw materials, and finally Li x+3 Fe x-y Mg y V 2-z Zn z (PO 4 ) 3 / C (x=4, y=0, z=0) lithium-ion battery positive electrode material.

[0071] The material obtained in this embodiment is LFVP / C material.

[0072] Comparative Example 2:

[0073] The method provided in Example 1 is used, the only difference being that the molar ratio of the raw materials is Fe:V:Zn:Mg=4:1:0.075:0.08, and finally the general formula Li x+3 Fe x-y Mg y V 2-z Zn z (PO 4 ) 3 / C (x=4, y=0.08, z=0.075) lithium ion battery positive electrode material.

[0074] Comparative Example 3:

[0075] The method provided in Example 1 is used, except that the molar ratio of the raw materials is Fe:V:Zn:Mg=3:1:0.05:0.06, and the final product is Li x+3 Fe x-y Mg y V 2-z Zn z (PO 4 ) 3 / C (x=3, y=0.06, z=0.05) lithium ion battery positive electrode material.

[0076] Comparative Example 4:

[0077] The method provided in Example 1 is used, except that the molar ratio of Fe:V:Zn:Mg in the raw materials is 2:1:0.05:0.04, and the final product is Li x+3 Fe x-y Mg y V 2-z Zn z (PO 4 ) 3 / C (x=2, y=0.04, z=0.05) lithium ion battery positive electrode material.

[0078] The LFMVZP / C material (i.e., a high-capacity zinc-magnesium ion-doped lithium vanadium iron phosphate positive electrode material) obtained in Example 1 and Comparative Examples 2 to 4 was used as a positive electrode material for a lithium-ion battery, mixed with a conductive agent (acetylene black) and a binder (PVDF) in a volume ratio of 8:1:1 to obtain a slurry, which was then coated on a metal aluminum current collector to obtain a positive electrode, and a polyolefin was used as a separator, a metal lithium was used as a counter electrode, and an electrolyte was 1 mol / L LiPF 6 As the solute, ethylene carbonate (EC) and diethyl carbonate (DEC) with a volume ratio of 1:1 were used as the solvent, and 5% fluoroethylene carbonate (FEC) was used as the additive. The lithium-ion battery was assembled in a glove box filled with argon.

[0079] The assembled lithium-ion battery was left to stand for 12 hours and then subjected to constant current charge and discharge tests. The charge and discharge voltage window was 2.5 to 4.3 V. The specific capacity, rate performance, and long cycle performance of the positive electrode of the lithium-ion battery were measured at room temperature.

[0080] The LFMVZP / C material obtained in Example 1 was characterized by the structure. Figure 1-2 As shown:

[0081] Figure 1 is the XRD pattern of the zinc and magnesium ion doped lithium vanadium iron phosphate positive electrode material in Example 1; Figure 1 As shown, all diffraction peaks of LFMVZP / C material are consistent with those of standard cards LVP JCPDS#:80-1515, LFP JCPDS#:81-1173, belonging to the monoclinic phase structure of pnma space group and no impurity peaks are detected, indicating that the introduction of zinc and magnesium ions does not affect the crystal structure of the material.

[0082] Figure 2 is a scanning electron microscope image of the zinc and magnesium ion doped lithium vanadium iron phosphate positive electrode material in Example 1; Figure 2 As shown, Zn 2+ Mg 2+ The particles of the doped samples are concentrated around 2 μm. The small particle size of the samples is conducive to the penetration of the electrolyte and has a positive effect on the electrochemical performance of the material. 2+ Mg 2+ The doping can refine the particle size of LFVP / C material, so the diffusion distance of lithium ions in the LFVP / C lattice structure is shortened, thereby improving the electrochemical performance of the material.

[0083] Figure 3 CV curve diagram of the zinc and magnesium ion doped lithium vanadium iron phosphate positive electrode material in Example 1; Figure 3As shown in the figure, the CV curve has 4 pairs of obvious redox peaks. The redox peaks of the LFMVZP / C material are sharp and symmetrical, with higher oxidation peak intensity and larger reduction peak area, which can provide more reversible capacity during the cycle.

[0084] Figure 4 2C constant current cycling performance diagram of the zinc and magnesium ion doped lithium vanadium iron phosphate positive electrode material in Example 1; Figure 4 As shown in the figure, the initial discharge capacity of the lithium-ion battery made of LFMVZP / C material is 118.35 mAh g at a current density of 2C. -1 After 50 cycles, the LFMVZP / C material can release 117.43 mAh g -1 The reversible capacity of Example 1 and Comparative Example 1 is shown in Table 1. The Coulomb efficiency during the cycle is close to 100%, with a high capacity retention rate of 99.22%, and good cycle stability.

[0085] Table 1: Effect data table of application example 1 and comparative example 1

[0086]

[0087] Figure 5 is the AC impedance spectrum of the zinc and magnesium ion doped lithium vanadium iron phosphate positive electrode material in Example 1; Figure 5 As shown, it can be seen that the modified lithium vanadium iron phosphate material has a smaller charge transfer resistance (Rct), faster lithium ion insertion / extraction kinetics, and easier electrode reaction.

[0088] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for modifying a high-capacity zinc-magnesium ion-doped lithium iron vanadium phosphate positive electrode material, characterized in that It is implemented as follows:

1. Weighing materials: According to the molar ratio of lithium, vanadium, iron, phosphorus, zinc, magnesium and carbon being (3.675-6.825):(0.95-1):(1.8-5):5.5:(0.01-0.05):(0.01-0.2):(4-8), respectively weigh a lithium source, a vanadium source, an iron source, a phosphorus source, a zinc source, a magnesium source and a carbon source; 2. Preparation of carbon-coated zinc and magnesium ion-doped lithium vanadium iron phosphate precursor materials: The weighed lithium source, vanadium source, iron source, phosphorus source, zinc source, magnesium source and carbon source are added into deionized water and stirred evenly to obtain a mixture, and then the mixture is dispersed into a dispersion medium, and then placed in a ball mill for 7 to 10 hours to obtain a slurry, and after drying and grinding, a carbon-coated zinc and magnesium ion-doped lithium iron vanadium phosphate precursor material is obtained; 3. Preparation of zinc and magnesium ion-doped lithium vanadium iron phosphate positive electrode materials: The carbon-coated zinc and magnesium ion-doped lithium iron vanadium phosphate precursor material is transferred to a tube furnace and subjected to gradient high-temperature calcination under an inert gas atmosphere. After the calcination, it is naturally cooled to room temperature, and then ground and sieved to obtain a high-capacity zinc and magnesium ion-doped lithium iron vanadium phosphate positive electrode material with a chemical formula of Li x+3 Fe x-y Mg y V 2-z Zn z (PO4)3 / C, and x=1-5, y=0.01-0.2, z=0.01-0.05, then the modification method is completed.

2. The method for modifying a high-capacity zinc-magnesium ion-doped lithium iron vanadium phosphate positive electrode material according to claim 1, characterized in that In step 1, the lithium source is lithium carbonate; the vanadium source is vanadium pentoxide; the iron source is ferrous oxalate dihydrate; the phosphorus source is ammonium dihydrogen phosphate; the zinc source is zinc oxide; the magnesium source is magnesium nitrate, magnesium acetate, magnesium sulfate or magnesium oxide; and the carbon source is sucrose, glucose or citric acid monohydrate.

3. The method for modifying a high-capacity zinc-magnesium ion-doped lithium iron vanadium phosphate positive electrode material according to claim 1, characterized in that In step 2, the dispersion medium is a hydrogen peroxide aqueous solution with a volume fraction of 1% to 5%; and the dispersion method is electromagnetic stirring.

4. The method for modifying a high-capacity zinc-magnesium ion-doped lithium iron vanadium phosphate positive electrode material according to claim 1, characterized in that The ratio of the total mass of the lithium source, vanadium source, iron source, phosphorus source, magnesium source, zinc source and carbon source to the volume of the dispersion medium in step 2 is 1 g: (5 mL to 15 mL).

5. The method for modifying a high-capacity zinc-magnesium ion-doped lithium iron vanadium phosphate positive electrode material according to claim 1, characterized in that The ball milling temperature in step 2 is 20-25° C., and the rotation speed is 400-600 r / min.

6. The method for modifying a high-capacity zinc-magnesium ion-doped lithium iron vanadium phosphate positive electrode material according to claim 1, characterized in that The ball mill in step 2 uses steel balls, agate balls or zirconia balls, and the ball-to-material mass ratio is 20:

1.

7. The method for modifying a high-capacity zinc-magnesium ion-doped lithium iron vanadium phosphate positive electrode material according to claim 1, characterized in that The drying in step 2: drying in a forced air drying oven at 80-120° C. for 12-15 hours; the grinding: grinding in an agate mortar for 20-30 minutes.

8. The method for modifying a high-capacity zinc-magnesium ion-doped lithium iron vanadium phosphate positive electrode material according to claim 1, characterized in that The gradient high temperature calcination in step 3 is as follows: heating to 300-400°C at a rate of 4-8°C / min and keeping warm for 6-10h; after the insulation, heating to 750-850°C at a rate of 4-8°C / min and keeping warm for 6-10h.

9. The method for modifying a high-capacity zinc-magnesium ion-doped lithium iron vanadium phosphate positive electrode material according to claim 1, characterized in that The inert gas in step three is argon; the sieving uses a 400-mesh sieve.

10. The method for modifying a high-capacity zinc-magnesium ion-doped lithium iron vanadium phosphate positive electrode material according to claim 1, characterized in that In step 3, high-capacity zinc-magnesium ion-doped lithium iron vanadium phosphate positive electrode material with a chemical formula of Li x+3 Fe x-y Mg y V 2- z Zn z (PO4)3 / C, and x=4, y=0.08, z=0.05.

Citation Information

Patent Citations

  • Method for preparing magnesium-doped xLiFePO4.yLi3V2(PO4)3 lithium ion battery anode material

    CN102208619A

  • LiFePO4 positive electrode material modified jointly by doping and coating and preparation method thereof

    CN104393291A

  • A metal element doped modified lithium manganese phosphate composite cathode material and a preparation method thereof

    CN109119615A

  • Method for preparing composite phosphate lithium battery postive electrode material

    CN112047321A

  • Sodium-phase-rich zinc vanadium sodium phosphate composite material as well as preparation and application thereof

    CN114156470A